Newly Synthesized N-Substituted Thiosemicarbazone as a Potential Corrosion Inhibitor for Mild Steel in 1 M HCl - Z. Nor Hashim, N; Kassim, K; H. Zaidon, F (International Journal of Engineering and Technology, 2019)
Two N-substituted thiosemicarbazone derivatives namely as 2-(4-chlorobenzylidene)-N-phenylhydrazinecarbothioamide and 2-benzylidene-N-phenylhydrazinecarbothioamide (L1 and L2, respectively) have been tested as corrosion inhibitors on mild steel in 1 M HCl. The ligands were synthesized and investigated using potentiodynamic polarization (PD) and electrochemical impedance spectroscopy (EIS).Â  The obtained results indicated that inhibition efficiency, (IE, %) L1 increased with increasing inhibitor concentrations which behaved as a good corrosion inhibitor compared to L2. The synthesized ligands were successfully characterized by melting point, elemental analysis (C, H, N, and S), Fourier-transform infrared spectroscopy (FT-IR) and NMR (1H and 13C) spectroscopy. The excellent inhibition effectiveness for both compounds on mild steel before and after immersion in 1 M HCl solution containing 40 ppm of L1 and L2 were also verified by scanning electron microscope (SEM). Based on potentiodynamic polarization results, it can be concluded that all investigated compounds are mixed-type inhibitors and obey the Langmuir adsorption isotherm.Â